2021
DOI: 10.6007/ijarbss/v11-i2/8844
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Principals’ Strategic Leadership on Students’ Outcome

Abstract: The principal strategic leadership strongly influences school performance, especially on students' achievement in academic, co-curriculum and personal. Various training and leadership courses are held for the principals to ensure that this group can translate it into strategically planned efforts thus producing excellent schools. In the Malaysian education context, there are three (3) elements of students' outcome, namely academic, co-curriculum and personality, which depend on a good and strategic principal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Furthermore, the results are paralleled to the findings of the study conducted by Mohammad and Ismail (2018) revealing that there are many factors that influence the principal strategic leadership and students' outcome. Zakaria et al (2021) concluded that the principal's individual strengths and their strategic planning are dominant factors. More so, the principal strategic leadership strongly influences school performance, especially on students' achievement in academic, co-curriculum and personal.…”
Section: Extensivementioning
confidence: 99%
“…Furthermore, the results are paralleled to the findings of the study conducted by Mohammad and Ismail (2018) revealing that there are many factors that influence the principal strategic leadership and students' outcome. Zakaria et al (2021) concluded that the principal's individual strengths and their strategic planning are dominant factors. More so, the principal strategic leadership strongly influences school performance, especially on students' achievement in academic, co-curriculum and personal.…”
Section: Extensivementioning
confidence: 99%
“…It is because often a student needs help to hone this. After all, he has no media or partner to do this, as with children with other field achievements (Zakaria et al, 2021).…”
Section: Carrying Out Special Coaching For Outstanding Studentsmentioning
confidence: 99%